Measurement of contrast and spatial resolution for the photothermal imaging method - Kim, Moojoong; Yoo, Jaisuk; Kim, Dong Kwon; Kim, Hyunjung (Applied Sciences (Switzerland), 2019)
Analyzing the quality of images generated from an imaging method is essential for determining the limits and applicability of that method. This study analyzed the quality of images resulting from a photothermal imaging method by applying the line spread function and the modulation transfer function to the spatial resolution and contrast, on the basis of certain parameters of the photothermal imaging method for a copper-resin double-layered structure. The parameters are the ratio of the first-layer thickness to the thermal diffusion length (Lf /Ld) and the ratio of the pump-beam radius to the thermal diffusion length (Rb/Ld). The phase delay profile (edge response function, ERF) of the subsurface structure derived from the photothermal imaging method becomes dimensionless upon division by the thermal diffusion length; as the ratio Lf /Ld increases, the spatial resolution and contrast increase.
Keywords: Contrast; ERF; Image quality; LSF; MTF; Photothermal imaging; Spatial resolution